The long-term survival of the doublet regimen of concurrent chemoradiation therapy for locoregionally advanced nasopharyngeal carcinoma: a retrospective study - Zhi-Qiang Wang; Xu-Dong Feng; Chun-Lei Ge; Yi Yang; Na Liang; Qing Ye; Yang Fu; Jian Wei; Yong Zhang; Rong-Qing Li (Radiation Oncology, 2022)
Abstract Objective This study introduces innovative strategies, the doublet regimen of concurrent chemoradiotherapy, to ensure longer survival for locoregionally advanced nasopharyngeal carcinoma. Methods We retrospectively reviewed 104 locoregionally advanced nasopharyngeal carcinoma patients who underwent taxane combined platinum-based concurrent chemoradiotherapy in our center between January 2013 and December 2018. All statistical analyses were performed using the Kaplan–Meier method (SPSS 23.0). Different groups were compared with the Wilcoxon rank-sum test. Results Ultimately, 104 patients were selected for this study, including 18 and 86 who received either concurrent chemoradiation therapy alone or concurrent chemoradiation therapy plus adjuvant chemotherapy, respectively. The median follow-up time for progression free survival was 53.0 months (IQR 48.5–57.5). The 3-years progression-free survival (PFS), overall survival (OS), local–regional recurrence-free survival (LRRFS) and distant metastasis-free survival (DMFS) rates of the doublet regimen of concurrent chemotherapy for locoregionally advanced nasopharyngeal carcinoma were 85.9%, 96.0%, 96.0% and 90.8%, respectively. Additionally, we analyzed the subgroups and found that the 3-years PFS, OS, LRRFS and DMFS rates for stage III versus stage IVa were 97.8% versus 75.5% (P = 0.000), 100% versus 92.5% (P = 0.004), 100% versus 92.4% (P = 0.015) and 97.8% versus 82.8% (P = 0.002), respectively. During concurrent chemotherapy, acute chemotherapy adverse events of grade 3 or 4 was only 18.3%. Leukopenia was the most common acute chemotherapy adverse event (in 10 patients [9.6%]), followed by neutropenia (in 8 patients [7.6%]). Conclusion The doublet regimen of taxane plus platinum concurrent chemoradiotherapy resulted in improved long-term survival of locoregionally advanced nasopharyngeal carcinoma patients, especially for local control rate and warrants further prospective evaluation.